2020
DOI: 10.3389/fpsyg.2020.01249
|View full text |Cite
|
Sign up to set email alerts
|

Music Self-Efficacy for Performance: An Explanatory Model Based on Social Support

Abstract: Personal perceptions of self-efficacy are particularly relevant in the field of music performance, which is oriented toward the outward expressions of one's own ability through public performances. Within this context, a number of personal variables, including social support and performance anxiety, have been shown to be associated with musical success and are therefore relevant for research that seeks to understand the four sources of self-efficacy (mastery experiences, vicarious observation, verbal persuasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 74 publications
2
32
0
Order By: Relevance
“… Schneider and Chesky (2011) also found that college music students with less frequent experiences of performance anxiety reported greater perceived social support. Recently, Zarza-Alzugaray et al (2020) provided further evidence for the importance of social support (by family, teachers and peers) in the development of performance self-efficacy and the mediating role of MPA in the process, and pointed to the necessity of establishing true social support that acts as a motivator to face performance challenges.…”
Section: Discussionmentioning
confidence: 99%
“… Schneider and Chesky (2011) also found that college music students with less frequent experiences of performance anxiety reported greater perceived social support. Recently, Zarza-Alzugaray et al (2020) provided further evidence for the importance of social support (by family, teachers and peers) in the development of performance self-efficacy and the mediating role of MPA in the process, and pointed to the necessity of establishing true social support that acts as a motivator to face performance challenges.…”
Section: Discussionmentioning
confidence: 99%
“…The self-efficacy questionnaire, originally validated by Ritchie and Williamon (2011) has been used to assess the construct widely with music students, with direct relation to performance, and more widely with regard to the wider lives of musicians (Ritchie and Williamon, 2012;González et al, 2018;Zarza-Alzugaray et al, 2020). The Self-efficacy for Performing questionnaire consists of 9 items, several of which are reverse coded.…”
Section: Methodsmentioning
confidence: 99%
“…These latter aspects were taken into account in our self-efficacy tool, without ignoring the possible role they might play in certain elements of criticism of musical education, public performance, and the anxiety associated with the latter. Zarza-Alzugaray et al (2020) have shown how peer support plays a key role in helping boys cope with performance anxiety. A similar idea can be found in the study by Hendricks (2014), who attributed an improvement in girls' perceived self-efficacy over the course of a 3-day music festival to the support they perceived from peers (among other factors, and only when the level of performance was more noncompetitive).…”
Section: Discussionmentioning
confidence: 99%
“…Although clear evidence has been found for the influence exerted by parents, teachers and peers on the development of a musical career (Orejudo et al, 2020), practically no evidence has been gathered to ascertain whether the role played by these agents leads to an improvement in musical self-efficacy. Previous studies have shown the role they can play by strengthening other elements associated with success in a musical career, such as providing the trainee with a series of resources to help them handle performance anxiety (Zarza-Alzugaray et al, 2020), but no direct data has been provided regarding the relationship between the support coming from those agents and the development of the musical self-efficacy. Nevertheless, before we continue to address this study's goals, we proceed to analyze in further detail the role of social support in musical training.…”
Section: Musical Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation